The involvement of ERK1/2 and p38 MAPK in the premature senescence of melanocytes induced by H2O2 through a p53-independent p21 pathway. Issue 2 (February 2022) - Hou, Xiaoyuan; Shi, Jiaqi; Sun, Li; Song, Lebin; Zhao, Wene; Xiong, Xixi; Lu, Yan
Highlights: These findings have significant implications about the pathogenesis of vitiligo. The role of oxidative stress on the premature senescence melanocytes were studied. H2 O2 activates MAPK pathways to induce the premature senescence of melanocytes. The melanosome transfer function are damaged in senescent melanocytes. Abstract: Background: The pathogenesis of vitiligo is still unknown and oxidative stress is an important factor that can damage or incapacitate melanocytes. Objective: To investigate the role of oxidative stress in the premature senescence of melanocytes and their transfer of melanosomes. Methods: Cultured human melanocytes were treated with H2 O2 after which cell viability and apoptosis were assessed. We investigated whether exposure to H2 O2 induces premature senescence. RNA sequencing was used to screen aging-related signaling pathways. The expression of dendritic regulatory proteins, adhesion molecules and cell cytoskeletal proteins, as well as melanosome distribution were characterized. The ROS scavenger NAC was used to study the role of ROS in cell senescence and in melanosome transfer. Results: Cell viability decreased progressively and cell apoptosis increased after treatment with H2 O2 . H2 O2 treatment tended to induce premature senescence in melanocytes through a p53-independent p21 pathway. RNA sequencing analysis showed that H2 O2 treatment induced the differential expression of MAPK signaling pathway components. Western blotting and qRT-PCR confirmed that H2 O2 treatment increased the phosphorylation of ERK1/2 and p38 MAPK, which are involved in inducing the senescence of melanocytes, but not JNK. The expression of cell cytoskeleton and adhesion molecules decreased after H2 O2 treatment. p21 siRNA treatment reversed these changes. Treatment with NAC improved the premature senescence and the impaired melanosome transfer induced by H2 O2 . Conclusion: H2 O2 increases ROS levels, which activates the ERK1/2 and p38 MAPK pathways to induce the premature senescence of melanocytes through p21 via a p53-independent pathway and consequently disrupts melanosome transfer.